Crystallization and preliminary x-ray studies of NADPH-cytochrome P450 reductase. - Djordjevic, S (1995)
NADPH-cytochrome P450 reductase (CPR; NADPH:ferrihemoprotein reductase, EC 1.6.2.4) catalyzes the transfer of electrons to all known microsomal cytochromes P450. CPR is unique in that it is one of only two mammalian enzymes known to contain both flavin adenine dinucleotide (FAD) and flavin mononucleotide (FMN), the other being the various isoforms of nitric oxide synthase. Similarities in amino acid sequence and in functional domain arrangement with other key flavoproteins, including nitric oxide synthase, make CPR an excellent prototype for studies of interactions between two flavin cofactors. We have obtained diffraction-quality crystals of rat liver CPR, expressed in Escherichia coli and solubilized by limited proteolysis with trypsin. The crystals were grown in Hepes buffer (pH 7.0), containing polyethylene glycol 4500 and NaCl. The crystals belong to the orthorhombic space group P2(1)2(1)2(1), with unit cell dimensions a = 103.3 A, b = 116.1 A, and c = 120.4 A. If we assume that there are two molecules of the 72-kDa CPR polypeptide per asymmetric unit, the calculated value of Vm is 2.54 A3/Da.